Accounting for Spacers in the Mechanical Calculation of Flexible Wires for Overhead Lines and Switchgears - Yu. V. Bladyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
The mechanical calculation of flexible wires of overhead lines and switchgears, in which in-phase or phase-to-phase spacers are installed, is under consideration. Spacers are considered as concentrated loads acting on the split phase. The formulas for determining the sag are given for a different number of spacers as a function of their number and the coefficient of concentrated forces. This takes into account the difference in suspension heights, tension insulators strings, wind and ice loads. These formulas, being presented in a form that is convenient for consumers, can be used for computer execution of the mechanical calculation of flexible wires in different climatic regimes, both in the presence and in the absence of phase splitting. The errors of replacing the spacers with a distributed load are demonstrated. Formulas are proposed that give the smallest error when replacing spacers with a distributed load. The greater the value of the concentrated forces from the tap-off lines and loops, the greater the error in calculating the sag of the switchgears wires. Therefore, it is not possible to replace them with a distributed load obtained by simply dividing the total load by the length of the span in the presence of the tap-off lines and loops.